Ecological Niche Modeling Approaches to Conservation of Endangered and Threatened Birds in Central and Eastern Europe - Papes, Monica (Biodiversity Informatics, 2007)
Comprehensive biodiversity surveys are unavailable for most Central and Eastern European countries. Although birds in general are well-studied, distributional information in the region is sparse and largely out-of of-date; I used museum specimen locality records and raster GIS data layers summarizing environmental dimensions to produce distributional hypotheses for the 36 threatened and endangered bird species in the region using ecological niche modeling. These ecological niche models were also used to predict likely future (2055) distributional shifts owing to global climate change. The entire suite of distributional information that resulted was used to evaluate strategies for conservation via simple heuristic place-prioritization algorithms based on complementarity and rarity considerations. These analyses identified priority areas in southern and eastern Romania, as well as other areas across the region, as priority targets for conservation action in the region.